(untitled) (Forum for Linguistic Studies, 2024)
Background: Thalassemia is an autosomal recessive disorder which is affecting the synthesis of hemoglobin. The children with thalassemia need lifelong blood transfusion and hospitalizations to manage the complications. Due to the continuity in care of children with thalassemia, the parents experiences various levels of psychosocial issues. Financial burden is also very common specially in lower- and middle-income countries. Multiple studies reported that around 23,000 as thalassemia major and 90% of these children are born in low or middle-income countries (LMICs) Materials and Methods: The PICO framework was used to operationalize the review question into key concepts. The entire review process followed PRISMA guidelines 2020. Study selection was done through various electronic databases like PubMed, PsychINFO, CINAHL, Scopus and Cochrane library. The studies included in the systematic review were also searched from various websites, organizations like Thalassemia International Federation and from citation searches through ancestry and descendancy approaches. The studies were selected according to the set inclusion and exclusion criteria. The inclusion and exclusion criteria was set with PICo format (Population, phenomena of interest and context). The quality assessment for the studies selected for the review was done with Joanna Briggs Institute tools (JBI) and QUADAS-2 tool. There was minimal risk of bias in the studies were noted. 13 studies were finally selected for the review. Results: To synthesize the findings, results were qualitatively summarized. No statistical analysis were done. The various results were categorized under the headings, Psychological issues, social issues, financial issues and care giver burden. Majority of the parents have stress, anxiety, guilty, depression and also psychosomatic symptoms. A multidisciplinary approach to managing the disease and psychosocial support is required for the management of thalassemia and to minimize the burdens on both patients and families.